PROSES PENYIDIKAN KECELAKAAN LALU LINTAS KORBAN MENINGGAL DUNIA DENGAN ANAK SEBAGAI TERSANGKA DI POLRES JEPARA - Manurung, Hendra Wijaya (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Handling traffic accidents is one of the implementation of the duties and functions of the Republic of Indonesia Police. The increasing number of traffic accidents in the Jepara Police jurisdiction every year, especially traffic accidents involving children as suspects, requires handling in accordance with the provisions of the applicable laws. This study analyzes the process of investigating a traffic accident victim who died with a child as a suspect at the Jepara Police. The problems raised in this research include a description of the occurrence of a traffic accident involving a death victim involving a child as a suspect at the Jepara Police, the process of investigating a traffic accident involving a death victim involving a child as a suspect at the Jepara Police and factors that influence the investigation of the accident unit. Then the Jepara Police for a traffic accident the victim died with a child as a suspect. This research uses a qualitative approach with a normative juridical approach with analytical descriptive research specifications. The theories used are management theory, law enforcement theory, traffic management concepts, traffic accident concepts, factors causing traffic accidents as well as concepts and rights. children in conflict with the law. This study discusses the factors that cause many accidents to occur in the jurisdiction of the Jepara Police. Next, we discuss the process of investigating traffic accidents involving fatalities involving children as suspects at Jepara Police, which is not in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Then finally analyze legal factors; law enforcement factors; facilities and facilities factors; community factors; and cultural factors that influence the process of investigating traffic accidents where victims die with children as suspects at Jepara Police.